THE IMPLEMENTATION OF SHARIA AUDIT IN INDONESIA: A SYSTEMATIC LITERATURE REVIEW - Khairul Saleh L. Tobing; Syamsudin; Muhammad Nur; Kumba Digdowiseiso (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Through a literature study, this study employs a Systematic Literature Review (SLR) approach to investigate the implementation of sharia auditing in Indonesia. The primary goal of the study is to comprehend the impact of financial report accessibility on regional financial management accountability in the context of sharia audits. Identifying related journals entails identifying ten accredited national journals that are relevant to the research topic. According to research data, only 17.54% of total Public Accounting Firms (KAP) in Indonesia use Sharia as a basis for audits. A significant issue in sharia audit practices is a lack of auditor expertise and understanding of sharia principles. The sharia audit process is also inefficient, negatively impacting the level of sharia compliance. Recommendations include increasing auditor competency and optimizing the sharia audit process. Furthermore, the implementation of sharia audits in sharia financial institutions faces the complexities of global modernity. Contemporary Islamic thought with Maqashid Syariah is expected to respond to this challenge and spur product innovation. Creating a consistent Sharia audit framework necessitates international collaboration.